Infection of healthcare workers despite a high vaccination rate during the fifth wave of COVID-19 due to Omicron variant in Hong Kong. Issue 1 (March 2023) - Wong, Shuk-Ching; Chan, Veronica Wing-Man; Yuen, Lithia Lai-Ha; AuYeung, Christine Ho-Yan; Leung, Jessica Oi-Yan; Li, Chi-Kuen; Kwok, Monica Oi-Tung; So, Simon Yung-Chun; Chen, Jonathan Hon-Kwan; Chiu, Kelvin Hei-Yeung; Tam, Anthony Raymond; Hung, Ivan Fan-Ngai; et al.
Summary: Background: No nosocomial infection was recorded in our healthcare workers (HCWs) during the early phase of the coronavirus disease 2019 (COVID-19) pandemic. With the emergence of the Omicron variant of increased transmissibility, infection in HCWs occurred as expected. We aimed to study the epidemiology of infection in HCWs and to describe the infection control measures during the outbreak of the Omicron variant. Methods: With daily rapid antigen testing and molecular confirmation test for COVID-19, infected HCWs were interviewed by infection control nurses (ICNs) to investigate the potential source of infection. The epidemiology of COVID-19 in Hong Kong served as reference. Results: During the fifth wave of COVID-19 (31 December 2021 to 31 May 2022), 1, 200, 068 cases were reported (incidence 95 times higher than in preceding waves in Hong Kong; 162, 103 vs 1, 707 per million population respectively, P <0.001). The proportion of infected HCWs was significantly higher than that of the general population (24.9%, 1, 607/6, 452 vs 16.2%, 1, 200, 068/7, 403, 100 respectively; P <0.01). The proportion of infected non-clinical staff was significantly higher than that of clinical staff (31.8%, 536/1, 687 vs 22.5%, 1, 071/4, 765 respectively; P <0.001). Of 82.8% (1, 330/1, 607) infected HCWs interviewed by ICNs, 99.5% (1, 324/1, 330) had been fully vaccinated; 49.5% (659/1, 330) had no identifiable source; 40.7% (541/1, 330) were probably infected from household members; 9.8% (130/1, 330) had possible exposure to confirmed patients or HCWs, but no lapse in infection control measures or inappropriate use of personal protective equipment was recalled. Conclusion: Omicron variant is highly transmissible such that breakthrough infection occurred despite high level of vaccination.